PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA INDOMARET NAROGONG DAYEUH CILEUNGSI - M Albend Pranata; Yudi Wibowo (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the effect of service quality and price on customer satisfaction. The method used is descriptive quantitative method. The data collection instrument used a questionnaire. The independent variables are service quality and price, while customer satisfaction is the dependent variable. All statements are valid, reliable, and normal. The effect of service quality and price on customer satisfaction, based on the tests carried out, the results of this study indicate that the reliability value can be seen that the service quality variable (X1) is 0.939, the price variable (X2) is 0.912. Service quality (X1) and price (X2) have a very strong relationship with customer satisfaction, it can be seen from the R Square value of 0.849, which shows that the independent variable consisting of service quality and price can be explained by customer satisfaction 84.9% is able to explain the independent variable, namely customer satisfaction (Y) while the remaining 15.1% is influenced by other variables not examined in this study. Service quality and price have a positive and significant effect on customer satisfaction at Indomaret Narogong Dayeuh Cileungsi.